PENGEMBANGAN INSTRUMEN PENILAIAN METAKOGNISI SISWA SEKOLAH MENENGAH PERTAMA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA PADA POKOK BAHASAN TEOREMA PYTHAGORAS KELAS VIII - Wisnanti, Arum; Sunardi, S; Trapsilasiwi, Dinawati (Kadikma, 2014)
Abstract.Metacognitionis thestudents' understanding of their weaknessesandstrengthsin learningandself-regulating during they are study, such asplanning, use andevaluationprocess. The research purposes are knowing process and result of development of instruments assessment junior high school students’ metacognition in solving mathematical story problems on the topic of pythagoras theorem in class viii. Instruments assessmentdevelopment model refers to Plomp model. Based on validation process and tryout the instruments assessment can be concluded that the learning sets had been appropriate with validate, reliable and practicecriteria. The result of the researchshows that the instruments satisfy the criteria of validity coefficient reaches 0,92, the reliability coefficient 0,8 andthe practicality percentage reaches 100 %. Key Words:instruments assessment, metacognition, problem solving